Does rural-to-urban migration place adolescents at risk of deleterious sexual and reproductive health outcomes?: Evidence from Haiti - Heckert, Jessica (Cambridge University Press, 2016)
This study examines the links between migration and sexual and reproductive health among rural-to-urban migrant youth in Haiti. It evaluates behavioural, knowledge and attitudinal components from the perspective of three competing explanations for migrants’ behaviours: adaptation, disruption and selection. Discrete-time event history analysis is employed to compare these hypotheses using Haiti Demographic and Health Survey data (N=1215 adolescent girls,N=829 adolescent boys). Multi-level models are used to compare changes in knowledge and attitudes in individuals using data from the Haiti Youth Transitions Study (N=223). The findings reveal that disruption is the most plausible explanation for the timing of migration and first sex among girls. However, contrary to the assumption that migrant youth risk experiencing first sex earlier, girls are less likely to experience first sex near the time they migrate, and rural-to-urban migrant boys may experience first sex at later ages. The high aspirations of migrant youth provide a likely explanation for these findings. Furthermore, male migrants accumulate less protective knowledge, which is consistent with the disruption hypothesis, and migrants endorse premarital sex similarly to non-migrants. Sexual and reproductive health curricula should be adapted to the unique needs of migrant youth, and youth should be targeted before they migrate.